2011
DOI: 10.1186/1471-2369-12-10
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of the canadian kidney disease cohort study (CKDCS): A prospective observational study of incident hemodialysis patients

Abstract: BackgroundMany nephrology observational studies use renal registries, which have well known limitations. The Canadian Kidney Disease Cohort Study (CKDCS) is a large prospective observational study of patients commencing hemodialysis in five Canadian centers. This study focuses on delineating potentially reversible determinants of adverse outcomes that occur in patients receiving dialysis for end-stage renal disease (ESRD).Methods/DesignThe CKDCS collects information on risk factors and outcomes, and stores spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In this analysis, participants were followed for up to 2 years or until death, migration outside the study region, or withdrawal of consent, whichever came sooner. Details of the Canadian Kidney Disease Cohort Study are presented elsewhere (15).…”
Section: Participantsmentioning
confidence: 99%
“…In this analysis, participants were followed for up to 2 years or until death, migration outside the study region, or withdrawal of consent, whichever came sooner. Details of the Canadian Kidney Disease Cohort Study are presented elsewhere (15).…”
Section: Participantsmentioning
confidence: 99%
“…We conducted a secondary analysis of data from the Canadian Kidney Dialysis Cohort Study (CKDCS) [16]. The CKDCS is a large, prospective observational study of all consenting adults commencing hemodialysis treatment in multiple ethnically diverse major centres across Canada [16].…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a secondary analysis of data from the Canadian Kidney Dialysis Cohort Study (CKDCS) [16]. The CKDCS is a large, prospective observational study of all consenting adults commencing hemodialysis treatment in multiple ethnically diverse major centres across Canada [16]. CKDCS was conducted according to the principles of the Declaration of Helsinki and approved by the ethics boards of each participating centre [16].…”
Section: Methodsmentioning
confidence: 99%
“…Diabetic nephropathy (DN) and retinopathy represent the major causes of end-stage renal disease and blindness (1-2) in developed countries. DN is associated with an increased risk of hypertension, adverse cardiovascular events (3), chronic kidney diseases and haemodialysis (4). Efforts are therefore being made to find ways of preventing and/or slowing down the progression of DN worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Although albuminuria is a useful clinical marker, tubulointerstitial fibrosis and tubular atrophy represent a better predictor of nephropathy progression because of their close association with declining renal function (5). Many randomized controlled trials have shown the efficacy of optimal glycemic control and RAS blockade in the primary and secondary prevention of DN (4,(7)(8)(9). The former is easily understood, as decreased "glucotoxicity" reduces end-organ damage.…”
Section: Introductionmentioning
confidence: 99%